2016
DOI: 10.1039/c6cc08197e
|View full text |Cite
|
Sign up to set email alerts
|

Cellular delivery of enzyme-loaded DNA origami

Abstract: In this communication, we show that active enzymes can be delivered into HEK293 cells in vitro when they are attached to tubular DNA origami nanostructures. We use bioluminescent enzymes as a cargo and monitor their activity from a cell lysate. The results show that the enzymes stay intact and retain their activity in the transfection process. The method is highly modular, which makes it a compelling candidate for a great variety of delivery applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 51 publications
0
51
0
2
Order By: Relevance
“…[ 25–27 ] Therefore, DONs have been increasingly employed for developing novel drug delivery systems [ 28,29 ] due to their versatile designability, high solubility, and intrinsic biocompatibility. [ 30–37 ] Moreover, certain types of DONs have been proven to be readily rapidly internalized by mammalian cells despite their negatively charged surface property. [ 38 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 25–27 ] Therefore, DONs have been increasingly employed for developing novel drug delivery systems [ 28,29 ] due to their versatile designability, high solubility, and intrinsic biocompatibility. [ 30–37 ] Moreover, certain types of DONs have been proven to be readily rapidly internalized by mammalian cells despite their negatively charged surface property. [ 38 ]…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30] These examples cover logic-gated nanorobots for modulating cell signaling, [31] structures for delivering anticancer drugs [32][33][34] and for circumventing drug-resistance, [35,36] as well as carriers equipped with siRNA molecules, [37] CpGtriggers, [38] and functional enzymes. [39] Despite this progress, it has been observed that the transfection of DNA structures is generally low [40] and that these objects are prone to degradation in biological environment. [41] Nevertheless, there exist techniques to presumably enhance both stability and transfection rates of the DNA structures by utilizing different sophisticated protection and coating mechanisms, such as virus protein [42] or lipid membrane encapsulation.…”
Section: Doi: 101002/adhm201700692mentioning
confidence: 99%
“…Just ten years after their introduction, DNA origami nanostructures are widely used in various fields of applied and fundamental research. Nowadays, DNA origami act as masks in molecular lithography, templates for nanoelectronic and plasmonic device fabrication, as delivery vehicles in molecular medicine, and substrates for single‐molecule experiments . Many of these applications rely on an intact and well‐defined shape as well as tailored mechanical properties of the DNA origami.…”
mentioning
confidence: 99%